2008
DOI: 10.1590/s0074-02762008000400018
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular identification of Leishmania chagasi from a bat (Carollia perspicillata) in northeastern Venezuela

Abstract: This report describes the isolation of a Leishmania chagasi strain from a bat (Carollia perspicillata), and its identification using biological methods and molecular characterization. The parasites were isolated in an artificial culture medium from a blood sample extracted from a bat heart. The isolate was then inoculated into the footpads of Balb/c mice, which subsequently developed a typical nodular leishmanial lesion; the parasites were confirmed as Leishmania by smear and histopathology. Molecular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 7 publications
1
24
0
4
Order By: Relevance
“…However, bats in the New World were repeatedly investigated and found infected with Leishmania species pathogenic to humans. In our study, the prevalence reached 5% (8 out of 163) corresponds with the infection rates of bats recorded in Sao Paulo, Brazil (4%) (Savani et al, 2010); while higher prevalence has been detected in Venezuela (9%) (Lima et al, 2008); Mexico (9.8%) (Berzunza-Cruz et al, 2015) and Mato Grosso do Sul, Brazil (40%) (Shapiro et al, 2013). Four of the positive bats were captured in the Aba-Roba and Awash-Methara leishmaniasis endemic foci while the other four specimens originated from non-endemic localities of Metu, Bedele and Masha (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, bats in the New World were repeatedly investigated and found infected with Leishmania species pathogenic to humans. In our study, the prevalence reached 5% (8 out of 163) corresponds with the infection rates of bats recorded in Sao Paulo, Brazil (4%) (Savani et al, 2010); while higher prevalence has been detected in Venezuela (9%) (Lima et al, 2008); Mexico (9.8%) (Berzunza-Cruz et al, 2015) and Mato Grosso do Sul, Brazil (40%) (Shapiro et al, 2013). Four of the positive bats were captured in the Aba-Roba and Awash-Methara leishmaniasis endemic foci while the other four specimens originated from non-endemic localities of Metu, Bedele and Masha (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Importantly, being cave-dwelling organisms, bats and sand flies frequently share living habitats where ample opportunity exists for sand flies to feed on bats (Feliciangeli, 2004). Natural Leishmania infection in bats has been reported in New World leishmaniasis foci and the findings suggested their possible epidemiological involvement in the transmission cycle (Lima et al, 2008;Savani et al, 2010;Shapiro et al, 2013;Berzunza-Cruz et al, 2015). Despite the attempts else where (Millan et al, 2014;Rotureau et al, 2006;Rajendran et al, 1985;Mutinga, 1975;Morsy et al, 1987), the extent of Leishmania natural infection in the Old World bats remains uncertain, and cases of Chiropteran Leishmania infections have not been documented in Ethiopia until now.…”
Section: Introductionmentioning
confidence: 99%
“…chagasi and L . amazonensis [52], [53] and should not be ignored in the search for sylvatic reservoirs of L . ( V .)…”
Section: Discussionmentioning
confidence: 99%
“…There is only one report of the isolation of Leishmania parasites ( L. infantum ) from the blood of a short-tailed fruit bat Carollia perspicillata in Venezuela (De Lima et al., 2008) (Table 1). Before that, Lampo et al had demonstrated that bats could be sources of blood for Lutzomyia longipalpis in Venezuelan caves (Lampo et al., 2000).…”
Section: Leishmania Hosts and Putative Reservoirsmentioning
confidence: 99%